Application of stiffness geometries in the lightweight design and optimization of automotive monolithic deep-drawn hard-shell rooftops - Chirinda, Gibson Pasbel (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.